TEACHING BIOLOGY BASED ON MODERN INFORMATION AND COMMUNICATION TECHNOLOGIES: IN THE DEVELOPMENT OF NEW UZBEKISTAN - Quvonchbek Xaitboev; Uringul Xaitboeva (Bright Mind Publishing, 2025)
The modernization of the educational process in New Uzbekistan requires the active integration of information and communication technologies (ICT) into the teaching of natural sciences, particularly biology. Biology, as a subject that combines theory with experimentation and real-world application, benefits significantly from digital tools that enhance visualization, interactivity, and personalized learning. This article explores the methodological foundations of teaching biology using ICT in the context of educational reforms in Uzbekistan. It analyzes the benefits of digital simulations, virtual laboratories, multimedia platforms, and interactive software that improve student engagement and conceptual understanding. The research highlights the pedagogical transformation underway in pedagogical higher education institutions, focusing on equipping future biology teachers with the necessary digital competencies. Furthermore, it outlines challenges such as technical infrastructure limitations and lack of methodological training, offering recommendations for overcoming these obstacles. The article ultimately emphasizes that incorporating ICT into biology education not only aligns with global trends but also serves as a catalyst for educational quality and innovation in New Uzbekistan.
Keywords: Biology education, information and communication technologies, pedagogical universities, virtual laboratories, digital teaching tools, educational innovation.